The antecedents of Muslim customers' behavioral intention towards Islamic mobile payment - Exval Mahendra Saputro; Sri Rahayu Hijrah Hati (Faculty of Economics, Universitas Islam Indonesia, 2021)
Purpose – The aim of the study is to identify the antecedents of the Indonesian Muslim customers' intention to use Islamic mobile payments.Methodology – The data were collected from 437 respondents, i.e., 216 potential users and 221 actual users of Islamic mobile payments. The data were analyzed using a partial least squares structural equation model (PLS-SEM).Findings – The study shows that performance expectancy, perceived religiosity obligation, compatibility, and perceived trust had positive effects on the behavioral intention of Muslim customers. For multi-group analysis, perceived religiosity obligation and compatibility have a significant effect on actual and potential users. Perceived trust significantly influences actual users' behavioral intentions, whereas social influence only significantly affects potential users.Originality – The study was conducted on Islamic mobile payment using actual users and potential users as respondents. The study will contribute to the development of theories on the adoption of technology and Muslim consumers.